No party now politics in the Civil War North - Smith, Adam I. P. (Oxford University Press, 2006)
Fiercely fought elections co-existed with a desire for patriotic unity in the Civil War North, creating a tension that was exploited by the dominant Republican party. This book explores the implications of this kind of politics for popular political participation, the construction of nationalism, and for Union victory.